Factores asociados al afrontamiento psicológico frente a la experiencia de la migración interna, en un grupo de estudiantes de pregrado pertenecientes a la Fundación Jaime Benítez Tobón en Bogotá (2021)
This research focuses on the factors associated with the coping and adaptation of a group of young people who have migrated internally to the city of Bogotá, to undertake an undergraduate degree at different universities in the Colombian capital, and in this way analyzes the different Factors associated with coping with the migratory process.